The Umayyad Caliphate in Andalusia: Its Diplomatic Relations with the German Empire (316-366 / 929-976) - Mahrat, Isam Miloud; Abdul Hamid, Faisal Ahmad Faisal (Journal Al-Muqaddimah, 2017)
Al Andalous witnessed in the era of caliphate variety in Foreign affairs which have not been found in any other era of its different ages. This study aims to study the impact of its diplomatic relation with German Empire. The present study will interest in discussing both political exchange and economic exchange. In this research, the researcher will follow the descriptive, analytical approach because it is considered a method that convenient with the nature of the study. Additionally, the historical approach as a supplementary method. By adopting these two approaches to conform the nature of social science studies. As for the study to reach the most important findings that result from these relations of the two countries where the most significant findings enabled the Umayyad Caliphate at Al Andalous with its relationship with German to fight off the danger of the Franks.